Clinical impact of proteinuria on renal function and treatment outcomes in patients with radioiodine-refractory thyroid cancer treated with lenvatinib - Naoki Fukuda; Kazuhisa Toda; Hirotaka Suto; Ryosuke Oki; Xiaofei Wang; Tetsuya Urasaki; Yasuyoshi Sato; Kenji Nakano; Makiko Ono; Junichi Tomomatsu; Hiroki Mitani; Shunji Takahashi (Endocrine Journal)
Proteinuria has been described as a major on-target adverse event of lenvatinib, although its long-term impact on renal function and clinical outcomes remains unclear. We conducted a retrospective observational study to assess renal function and prognosis in patients with radioiodine-refractory differentiated thyroid cancer (RR-DTC) receiving lenvatinib. Overall, 70 patients with RR-DTC treated with lenvatinib were enrolled. When proteinuria was observed, the dose and schedule of lenvatinib were adjusted to achieve a urine protein-to-creatinine ratio (UPCR) of less than 3.5 g/gCre according to the study protocols of recent pivotal trials. In total, 50 (71%) and 25 (36%) patients presented with any-grade and grade 3 proteinuria, respectively. Multivariate analysis revealed that age [>65; odds ratio (OR) 8.24, 95% confidence interval (CI) 1.74–39.00, p < 0.01], history of diabetes mellitus (OR 7.79, 95% CI 1.31–46.20, p = 0.02), and hypertension (OR 4.07, 95% CI 1.22–13.60, p = 0.02) were significantly associated with the development of grade 3 proteinuria. Overall, the median estimating glomerular filtration rate (eGFR) gradually decreased every 3 months during treatment. However, no significant deterioration in eGFR was observed in patients with grade 3 proteinuria compared with patients with grades 0–2 proteinuria until 48 months. Patients who developed proteinuria had better survival outcomes than those without proteinuria. In conclusion, the proteinuria grade was not significantly associated with decreased eGFR under UPCR monitoring in our study. Therefore, lenvatinib can carefully be continued targeting UPCR of less than 3.5 g/gCre.